2018
DOI: 10.3390/su10072457
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Shedding from Textiles—Developing Analytical Method for Measurement of Shed Material Representing Release during Domestic Washing

Abstract: The topic of shedding of micro-sized polymeric particles, so called microplastics, from textiles has been covered by an increasing number of studies over the past years. However, the methods with which the shedding of microplastics from textiles has been measured so far has shown a large variation. Consequently, the results regarding the amount of shed particles also vary, from 120 to 728,289 particles from similar garments in recent studies. This article presents research enabling for identification of whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
86
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 14 publications
0
86
1
3
Order By: Relevance
“…The lack of visualization leads to the assumption that the entire material recovered on the filter is attributed to fibers only. However, studies confirmed the presence of fibers and particles from non-textile sources in wastewaters from laundry [23,27]. In this sense textiles are A) an emitting source of fibers as fiber shedding occurs, and B) serve as a carrier for adhered foreign fibers and particles of various materials, shapes and sources.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…The lack of visualization leads to the assumption that the entire material recovered on the filter is attributed to fibers only. However, studies confirmed the presence of fibers and particles from non-textile sources in wastewaters from laundry [23,27]. In this sense textiles are A) an emitting source of fibers as fiber shedding occurs, and B) serve as a carrier for adhered foreign fibers and particles of various materials, shapes and sources.…”
Section: Introductionmentioning
confidence: 95%
“…Improvements have been developed by De Falco et al counting fibers on SEM-images acquired in orthogonal direction of the filter and extrapolating to the complete surface [22]. Jönsson et al applied an automated software-based fiber counting of the filter surface using microscopy [23]. However, visual counting methods entail the risk of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations